PERSENTASE DOSIS KEDALAMAN (PERCENTAGE DEPTH DOSE) DENGAN PESAWAT TELETERAPI COBALT-60 FCC 8000 F DI RSUP SANGLAH DENPASAR - Christine Djara, Grace; Ratini, Ni Nyoman; Sudarsana, I Wayan Balik (BULETIN FISIKA, 2015)
Successful implementation of treatment using Cobalt-60 8000 F FCC, strongly influenced the precision and accuracy of the implementation is largely determined by the data PDD. Based on the research the value of PDD at a depth of 0 cm with a broad range of the field is at 39.7% - 48.5%, while the maximum value reached 100%  PDD found at a depth of 0.5 cm. The amount of deviation between the results of a study of the data and BJR Sanglah reached 5% at a depth of 8 cm by 6 cm wide field x 6 cm and 8 cm x 8 cm, and the smallest deviation value of 0.1% found in a wide field 6 cm x 6 cm with depth 7 cm. keywords : cobalt-60, the percentage depth dose, dispersion values